Procalcitonin as a marker of diabetic foot ulcer infection - Nabil A El-Kafrawy; Mohammed A Shaaban; Mohammed A Korany; Ahmed A Sonbol; Moustafa B Ata (SpringerOpen, 2019)
Background Procalcitonin (PCT), an amino acid protein precursor of calcitonin hormone released by thyroid C cells or other body cells, can be used as a marker for diagnosing infection. PCT has a suggestive role in diagnosing diabetic foot infection alone or in combination with other markers of infection. Objective The aim was to clarify the effectiveness of PCT as a marker for diagnosing of infection in Egyptian patients with diabetic foot ulcer (DFU) in comparison with other inflammatory markers such as C-reactive protein, white blood cell count, and erythrocyte sedimentation rate. Patients and methods This cross-sectional study was carried out at Menoufia University Hospitals, from the period of January 2018 to December 2018. In total, 90 patients were classified into three groups; each group contained 30 patients: group I served as diabetic control without foot ulcers, group II patients had noninfected DFU, and group III patients had infected diabetic foot ulcer (IDFU). Diagnosis of IDFU relied on Infectious Diseases Society of America-International Working Group on the Diabetic Foot classification of diabetic foot infection. Results Serum PCT levels were elevated in DFU groups, with significantly higher in infected more than noninfected DFU. In addition, PCT levels were significantly higher in patients with IDFU compared with traditional markers such as C-reactive protein, erythrocyte sedimentation rate, and white blood cell counts. Conclusion Based on our results, we conclude that PCT has a valuable role in diagnosing infection in DFUs.